2015
DOI: 10.1159/000441942
|View full text |Cite
|
Sign up to set email alerts
|

Non-Verbal and Verbal Fluency in Prodromal Huntington's Disease

Abstract: Background: This study examines non-verbal (design) and verbal (phonemic and semantic) fluency in prodromal Huntington's disease (HD). An accumulating body of research indicates subtle deficits in cognitive functioning among prodromal mutation carriers for HD. Methods: Performance was compared between 32 mutation carriers and 38 non-carriers in order to examine the magnitude of impairment across fluency tasks. The predicted years to onset (PYTO) in mutation carriers was calculated by a regression equation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
(102 reference statements)
0
7
0
1
Order By: Relevance
“…Phonemic, semantic and nonverbal fluency were assessed by Robins Wahlin et al [33] in a group of 16 distant-from-onset patients and 16 close-to-onset premotor patients and 38 controls. Statistically significant differences were found in all types of fluency when comparing HD-close patients to controls.…”
Section: Cognitive Symptomsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phonemic, semantic and nonverbal fluency were assessed by Robins Wahlin et al [33] in a group of 16 distant-from-onset patients and 16 close-to-onset premotor patients and 38 controls. Statistically significant differences were found in all types of fluency when comparing HD-close patients to controls.…”
Section: Cognitive Symptomsmentioning
confidence: 99%
“…However, HD-distant patients and controls did not differ in the remaining tasks; this might be due to the small sample size. Also, the authors showed a correlation between predicted years to onset (based on CAG repeats) and performance on all tasks [33]. …”
Section: Cognitive Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cautionary note concerns recent findings that FM100 performance is not purely a measure of colour discrimination but instead also reflects general nonverbal ability [42]. Given evidence that non-verbal fluency is reduced even in prodromal HD [43], the FM100 may not represent a suitable means of testing colour discrimination in this group.…”
Section: Colour Visionmentioning
confidence: 95%
“…Klinik olarak belirgin HH'da lisan fonksiyonları konuşma akıcılığı görevlerinin performansı, striatum, frontal loblar ve frontostriatal devrenin bütünlüğüne ve bir dereceye kadar temporal loblara bağlıdır [4]. Hastalık ilerledikçe bu döngülerdeki disfonksiyon artmakta ve hastanın konuşması anlaşılmaz hale gelebilmektedir [5].…”
Section: Introductionunclassified